Tindakan E-WOM Akibat Artificial Intelligence Warna Kosmetik Pada Kalangan Pengguna Sosial Media di Indonesia - Aura Auliya Ramadina; Sri Vandayuli Riorini (Peneliti.net, 2023)
Recent advances in smartphone technology and social media platforms have increased the popularity of artificial intelligence (AI) cosmetic colors. Meanwhile, Indonesia is a lucrative market for various beauty products and foreign technological innovations. This study aims to investigate the adoption of AI cosmetic color applications and electronic word-of-mouth (e-WOM) intentions in Indonesia. This study aims to investigate the adoption of AI in color cosmetic applications and electronic word-of-mouth (e-WOM) intentions in Indonesia. A questionnaire design was used in this study, where users of AI cosmetic colors in Indonesia in the 17- 45 year age category produced 100-200 respondents. To analyze the data, this study used the Structural Equation Modeling (SEM) method through SPSS and AMOS software. A 2-step approach, Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), was applied to prove the hypothesis and produce results. This study shows the findings that (1) Social media addiction is a positive predictor of AI color cosmetics usage, (2) AI color cosmetics usage is a positive predictor of actual purchase, (3) actual purchase is a positive predictor of e-WOM intention and finally, (4) there is a full mediating effect of the actual purchase.